2023
DOI: 10.1093/nar/gkad656
|View full text |Cite
|
Sign up to set email alerts
|

CRI-SPA: a high-throughput method for systematic genetic editing of yeast libraries

Abstract: Biological functions are orchestrated by intricate networks of interacting genetic elements. Predicting the interaction landscape remains a challenge for systems biology and new research tools allowing simple and rapid mapping of sequence to function are desirable. Here, we describe CRI-SPA, a method allowing the transfer of chromosomal genetic features from a CRI-SPA Donor strain to arrayed strains in large libraries of Saccharomyces cerevisiae. CRI-SPA is based on mating, CRISPR-Cas9-induced gene conversion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Moreover, our method can serve as a tool for genome-scale knockout screens to identify genomes with improved production phenotypes. While host-pathway interactions are normally seen as deleterious for production, it is well known that genetic knockouts can cause unexpected effects on cell physiology; for example, a large-scale study showed that a small fraction of double yeast knockouts can improve fitness 49 , while multiplexed CRISPR screens have found combinations of knockouts with improved metabolic phenotypes 50,51 . Such findings pave the way for the use of such synergistic genetic interactions as a novel strategy to improve production.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our method can serve as a tool for genome-scale knockout screens to identify genomes with improved production phenotypes. While host-pathway interactions are normally seen as deleterious for production, it is well known that genetic knockouts can cause unexpected effects on cell physiology; for example, a large-scale study showed that a small fraction of double yeast knockouts can improve fitness 49 , while multiplexed CRISPR screens have found combinations of knockouts with improved metabolic phenotypes 50,51 . Such findings pave the way for the use of such synergistic genetic interactions as a novel strategy to improve production.…”
Section: Discussionmentioning
confidence: 99%